Hubungan antara Epistemologi dan Logika Ilmiah dalam Pengembangan Pengetahuan Ilmiah - lutfi hidayah; Dodi Ahmad Haerudin (Jurnal Filsafat dan Teologi Katolik, 2026)
This study aims to analyze the relationship between epistemology and scientific logic in the development of scientific knowledge using a library research approach by reviewing relevant literature in the fields of philosophy of science, theory of knowledge, and principles of scientific logic. The findings indicate that epistemology serves as a philosophical foundation for understanding the origin, structure, and validity of knowledge, while scientific logic functions as a systematic tool that guides reasoning in constructing rational and consistent scientific truth. Both have a complementary relationship, where epistemology provides a normative framework for determining the criteria of knowledge validity, and scientific logic ensures that the reasoning process is structured, coherent, and free from fallacies. Therefore, the integration of epistemology and scientific logic plays a crucial role in producing scientific knowledge that is objective, measurable, and academically accountable, while also enhancing the overall quality and credibility of the scientific process.